Mass Balance, Metabolic Pathways, Absolute Bioavailability, and Pharmacokinetics of Giredestrant in Healthy Subjects - Kshirsagar, Smita; Chen, Ya-Chi; Yu, Jiajie; Gates, Mary R.; Kawakatsu, Sonoko; Khojasteh, S Cyrus; Ma, Shuguang; Musib, Luna; Malhi, Vikram; Osaghae, Uyi; Wang, Jing; Cho, Sungjoon; et al. (Drug metabolism and disposition, 2024)
Giredestrant is a potent and selective small-molecule estrogen receptor degrader. The objectives of this study were to assess the absolute bioavailability (aBA) of giredestrant and to determine the mass balance, routes of elimination, and metabolite profile of [14C]giredestrant. In part 1 (mass balance), a single 30.8-mg oral dose of [14C]giredestrant (105 µCi) was administered to women of nonchildbearing potential (WNCBP; n = 6). The mean recovery of total radioactivity in excreta was 77.0%, with 68.0% of the dose excreted in feces and 9.04% excreted in urine over a 42-day sample collection period. The majority of the circulating radioactivity (56.8%) in plasma was associated with giredestrant. Giredestrant was extensively metabolized, with giredestrant representing only 20.0% and 1.90% of the dose in feces and urine, respectively. All metabolites in feces resulted from oxidative metabolism and represented 44.7% of the dose. In part 2 (aBA), WNCBP (n = 10) received an oral (30-mg capsule) or intravenous (30-mg solution) dose of giredestrant. The aBA of giredestrant after oral administration was 58.7%. Following the intravenous dose, giredestrant had a plasma clearance and volume of distribution of 5.31 L/h and 266 L, respectively. In summary, giredestrant was well tolerated, rapidly absorbed, and showed moderate oral bioavailability with low recovery of the dose as parent drug in excreta. Oxidative metabolism followed by excretion in feces was identified as the major route of elimination of giredestrant. This study provides definitive insight into the absorption, distribution, metabolism, and excretion of giredestrant in humans. The results show that giredestrant exhibits low clearance, a high volume of distribution, and moderate oral bioavailability in humans. In addition, the data show that oxidative metabolism followed by excretion in feces is the primary elimination route of giredestrant in humans. These results will be used to further inform the clinical development of giredestrant.